Structural dynamics of basaltic melt at mantle conditions with implications for magma oceans and superplumes - Majumdar, Arnab (Nat Commun, 2020)
Transport properties like diffusivity and viscosity of melts dictated the evolution of the Earth’s early magma oceans. We report the structure, density, diffusivity, electrical conductivity and viscosity of a model basaltic (Ca(11)Mg(7)Al(8)Si(22)O(74)) melt from first-principles molecular dynamics calculations at temperatures of 2200 K (0 to 82 GPa) and 3000 K (40–70 GPa). A key finding is that, although the density and coordination numbers around Si and Al increase with pressure, the Si–O and Al–O bonds become more ionic and weaker. The temporal atomic interactions at high pressure are fluxional and fragile, making the atoms more mobile and reversing the trend in transport properties at pressures near 50 GPa. The reversed melt viscosity under lower mantle conditions allows new constraints on the timescales of the early Earth’s magma oceans and also provides the first tantalizing explanation for the horizontal deflections of superplumes at ~1000 km below the Earth’s surface.